2021
DOI: 10.5664/jcsm.8988
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and psychological treatments for chronic insomnia disorder in adults: an American Academy of Sleep Medicine systematic review, meta-analysis, and GRADE assessment

Abstract: Introduction:The purpose of this systematic review is to provide supporting evidence for a clinical practice guideline on the use of behavioral and psychological treatments for chronic insomnia disorder in adult populations. Methods: The American Academy of Sleep Medicine commissioned a task force of 9 experts in sleep medicine and sleep psychology. A systematic review was conducted to identify randomized controlled trials that addressed behavioral and psychological interventions for the treatment of chronic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
104
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(117 citation statements)
references
References 201 publications
(1,067 reference statements)
5
104
0
8
Order By: Relevance
“…Non-pharmacological management of sleep is the first-line treatment for sleep problems, but not all methods may be feasible within the time available [ 96 ]. The basic rules of sleep hygiene should be gone through in the preoperative visit with the patient.…”
Section: How To Improve Sleep Pre- and Postoperativelymentioning
confidence: 99%
See 1 more Smart Citation
“…Non-pharmacological management of sleep is the first-line treatment for sleep problems, but not all methods may be feasible within the time available [ 96 ]. The basic rules of sleep hygiene should be gone through in the preoperative visit with the patient.…”
Section: How To Improve Sleep Pre- and Postoperativelymentioning
confidence: 99%
“…In the preoperative evaluation, patients should be advised to maintain the regular circadian sleep–wake rhythm while at the hospital, if possible, and after discharge at home. Non-pharmacological techniques that are likely to improve sleep in both pre- and postoperative settings and which only need short practice include, for example, relaxation techniques, breathing exercises, and listening to music [ 96 , 97 , 98 , 99 ]. The availability of these techniques has significantly increased with the availability of internet-based programs.…”
Section: How To Improve Sleep Pre- and Postoperativelymentioning
confidence: 99%
“…Though this has to date only been demonstrated in patients with persistent insomnia, pilot studies have shown that cognitive therapy for insomnia has been associated with a reduction of worry, unhelpful beliefs, somatic arousal, selective attention and monitoring, and safety behaviors after treatment (Harvey et al, 2007 , 2014 ; Sunnhed et al, 2020 ). Regarding pre-sleep arousal, which predicted insomnia, relaxation techniques have been associated with beneficial effects on a number of clinical issues, including insomnia, depression, and anxiety (Jorm et al, 2008 ; Kim and Kim, 2018 ; Edinger et al, 2021 ). Whether patients with anxiety and depression might benefit from relaxation as a prevention intervention regarding insomnia, as a way of killing three birds with one stone, is an unanswered question.…”
Section: Discussionmentioning
confidence: 99%
“… 9 This is likely due in part by the numerous meta-analyses demonstrating robust clinical improvements across numerous sleep-related outcomes using individual, group, internet-based, and self-help CBT-I. 68 …”
Section: Introductionmentioning
confidence: 99%